Design of bow-tie patch antenna with and without U-slot on ground plane at resonant frequency 2.5GHz / Siti Norlihaina Mohd Razali - Mohd Razali, Siti Norlihaina (2016)
The main purpose of this paper is to design a bow-tie patch antenna with U-slot on ground plane at resonant frequency 2.5GHz. The designed was carried out at two different structures. First, designed the bow-tie antenna without slot and second, with slot on ground plane. The microstrip patch antennas were designed using 1.6mm FR-4 substrate with dielectric constant of 4.3 and loss tangent 0.025. The design were simulated by using CST Microwave Studio and measured by using Vector Network Analyser (VNA) for return loss and using Anechoic Chamber for the radiation pattern. The value for the return loss is increased from -24.659 to -25.537 dB for bow-tie patch antenna without slot on ground plane while the bow-tie antenna with slot on ground plane, the return loss is reduced from -31.833 dB to -30.478 dB but the resonant frequency is shifted from 2.5 GHz in simulation to 2.65 GHz and 2.64GHz in measurement.